Prediksi Klasifikasi Perawatan pada Dataset Kanker Payudara Coimbra Memakai Metode Naive Bayes - Ferawaty Ferawaty; Wenripin Chandra; Kelvin Ivanka (UNIVERSITAS PELITA HARAPAN, 2020)
Breast cancer is a dreaded disease and a major cause of death. In this study, the Naïve Bayes method is used to predict the category of breast cancer treatment for the Breast Cancer Coimbra Dataset. Test results involving nine variables in the dataset resulted in 44.8% of the